Fitness for commercial flying in a case of non-Hodgkin lymphoma: Aeromedical risk assessment - Jeya Karthik; Avinash Ballekere Krishnegowda; Suhani Maridoss (Indian Journal of Aerospace Medicine, 2026)
Non-Hodgkin lymphoma (NHL) comprises a category of malignant neoplasms that arise from lymphoid tissues, which primarily affect the lymph nodes. Histologically, diffuse large B-cell lymphoma (DLBCL) is the most common subtype of NHL. The various clinical manifestations depend on the site, stage, and extent of disease and are generally treated with Chemo-immunotherapy. A 39-year-old civil aircrew, diagnosed as a case of DLBCL, treated with chemo-immunotherapy (rituximab, cyclophosphamide, hydroxydaunorubicin, oncovin, and prednisolone regimen), after complete remission and drug-free status for 25-month duration, reported to an Indian Air Force boarding center for aeromedical evaluation and disposal. The survival rate post-treatment for DLBCL is 94% as per the International Prognostic Index. However, in the first 1–2 years, the recurrence rate is between 30 and 40%. Aeromedical concerns include treatment efficacy, recurrence/relapse, post-chemotherapeutic effects, aviation risk on disability, prognosis and follow-up duration, and investigations to be carried out. The risk assessment matrix was carried out in this case using 5-year prognosis survival, and the risk of incapacitation fell between 0.1% and 1%. The fitness for flying was considered on the basis of the incapacitation risk of